Understanding the dynamics of complexity: new insights for senior leadership practice in one higher education institution in England - Steed, Carol (2022)
The higher education sector in England is having to rethink how it will operate in the future. The speed and scale of change; uncertainty and ambiguity; emergence from a global crisis; and the increasing complexity of the environment the sector is operating in has challenged some of the traditional norms of leadership. With senior leaders, and in particular senior leadership teams, needing to take an active role in this re-engineering, many are recognising that the dial has been reset in terms of the leadership practices that have served them well for many years. Now more than ever it is clear that a greater emphasis needs to be placed on developing leaders who can lead complexity (Uhl-Bien 2021).